The future of mobile wireless communication networks - Li, X.C.; Gani, Abdullah; Salleh, R.; Zakaria, O. (2009)
The future of mobile wireless communication networks will be experienced several generations as which have been experienced. This kind of development will drive the researches of information technology in industrial area. In this paper, we predict the future generations of mobile wireless communication networks including 4th, 5th, 6th and 7(th) generations. The main objective of this paper is to propose a technical frame for industry in the future. Thus, this paper is focused on the specification of future generations of wireless mobile communication networks.